Biosynthesis of Silver Nanoparticles Using Cinnamomum tamala Leaf Extract and Revealing Its Antioxidant Activity - Farhana S, Shireen; Durairaj, Rohini; Chandrasekar, Shobana; Boopathy, Usharani (Journal of Neonatal Surgery, 2025)
Silver nanoparticles (AgNPs) possess distinctive properties. This study examines the biosynthesis of AgNPs with antioxidant properties using Cinnamomum tamala leaves through green chemistry. Silver nitrate (AgNO3) was converted to AgNPs mediated Cinnamomum tamala leaf extract method, providing a cost-effective and eco-friendly alternative to conventional methods. X-ray diffraction (XRD) confirmed the crystalline structure of AgNPs with an average size of 21.92 nm. Scanning electron microscopy (SEM) and Transmission electron microscopy (TEM) analyzed the nanoparticles' morphology and size distribution. The AgNPs were found to range from 30 to 60 nm, establishing their sub-100 nm size. The presence of AgNPs was verified by a peak at 3-3.5 keV in the EDX spectrum. Ultraviolet-visible (UV-Vis) spectroscopy and Fourier-transform infrared spectroscopy (FTIR) were employed to examine the reduction of AgNPs and stable phytochemicals. Various radical scavenging activities were evaluated to determine antioxidant capacity. The antioxidant activity was assessed through DPPH, superoxide anion, hydroxyl, hydrogen peroxide, and nitric oxide scavenging assays. AgNPs exhibited substantial antioxidant activity with IC50 values of 58.88µg/mL, 57.18µg/mL, 53.58µg/mL, 61.50µg/mL, and 56.02µg/mL respectively, indicating effective free radical scavenging. The results highlight the significant antioxidant properties of both the leaf extract and AgNPs. Synthesized AgNPs exhibited enhanced characteristics compared to the leaf extract. AgNPs from Cinnamomum tamala leaf extract show considerable potential as antioxidants for nutraceutical and pharmaceutical applications against oxidative stress-related diseases.